AUTOMATIC INFORMATION SYSTEM O F STEELMAKING OF RUP “BMZ” - D. S. Savkov; A. A. Katsubo (Литьë и металлургия)
The information system on basis of data manager ORACLE of steel production for increase of efficiency, control quality of workshops ESPTs-1,2 is developed and implemented at RUP “BMZ”.